Ocular Antihypertensive Medication Use After iStent Implantation Concurrent With Cataract Surgery vs Cataract Surgery Alone in a Large US Health Care Claims Database - Wang, Sophia Y; Singh, Kuldev; Stein, Joshua D; Chang, Robert T (JAMA ophthalmology, 2019)
The iStent Trabecular Micro-Bypass (Glaukos Corporation) is a minimally invasive glaucoma implant used in conjunction with cataract surgery to lower intraocular pressure. To determine whether implantation of the iStent concurrent with cataract surgery is associated with reduced use of ocular antihypertensive medications in a US health care claims database. Retrospective, observational longitudinal cohort study of individuals enrolled in a US managed care network who underwent iStent implantation with cataract surgery (iStent/CEIOL) from 2012 to 2016 (n = 1509 bilateral and n = 1462 unilateral surgery). A control group of individuals who underwent bilateral cataract surgery only (CEIOL) were matched 1:1 to patients undergoing bilateral iStent/CEIOL on baseline demographic and clinical factors. Data were analyzed between November 1, 2017, and January 31, 2018. The number of topical ocular antihypertensive agents used postoperatively by patients undergoing iStent/CEIOL compared with baseline and with matched CEIOL control individuals, and hazard ratios with 95% confidence intervals for sustained reduced use of at least 1 topical ocular antihypertensive agent postoperatively. Of the 2971 eligible enrollees, mean age at first surgery was 74.3 years, and 1659 (55.8%) were women. Patients undergoing iStent/CEIOL had diagnoses that included primary open-angle glaucoma (n = 2329; 78.4%), narrow angles (n = 381; 12.8%), and secondary glaucomas (n = 261; 8.8%). At baseline, 1223 (41.2%) were receiving no topical glaucoma agents; 876 (29.5%), 437 (14.7%), and 435 (14.6%) were receiving 1, 2, or at least 3 agents, respectively. Although only 678 persons (22.8%) completed at least 2 years of postoperative follow-up, the proportion of patients receiving no drops increased postoperatively (64.7%, 20-24 months, P < .001, χ2). Patients receiving at least 1 topical agent at baseline had mean reduction of 1.01 and 0.61 medications used at 20 to 24 months with bilateral or unilateral surgery, respectively (both P < .001, paired t). Sustained reduction in glaucoma medication use was more likely in patients receiving at least 3 vs 1 medication at baseline (hazard ratio, 1.68; 95% CI, 1.36-2.09). Compared with matched control individuals undergoing CEIOL, patients undergoing bilateral iStent/CEIOL had a greater mean reduction in drops used (0.99 vs 0.49; postoperative month 20-24; P < .001; paired t) and a higher proportion receiving no drops postoperatively (73.5% vs 55.3%, postoperative month 20-24; P < .001; χ2). Implantation of the iStent trabecular micro-bypass stent concurrent with cataract surgery was associated with moderately reduced use of topical ocular antihypertensive medication. Reduction in the use of glaucoma medications may lessen the burden of medication adverse effects and promote better adherence.